Public Infrastructure and Regional Resilience: Evidence from the 1918 Spanish Flu in Germany - Mona Foertsch; Felix Roesel (Center for Economic Studies and ifo Institute (CESifo), 2023)
Can public infrastructure help regions to mitigate large shocks? We examine how hospital infrastructure contributes to regional resilience in the event of serious health emergencies. During the 1918 Spanish flu pandemic, four out of every 1,000 Germans died. We find lower influenza mortality rates and no political reaction in cities and rural areas with adequate hospital infrastructure. In contrast, rural areas without adequate infrastructure absorb shocks poorly, and voters punish the governing parties in the next elections. We conclude that public infrastructure can mitigate large external shocks, especially in rural regions.
Keywords: D72; O18; I10; 330; public infrastructure; resilience; health shocks; Spanish flu; Germany